External evaluation of the ESAF : report - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
The study complements the Fund's latest internal ESAF review, which was discussed in the Executive Board of July 18, 1997, and subsequently published as IMF Occasional Paper No. 156: the ESAF at Ten Years (1997)
Includes bibliographical references (p. 126-129).
osc 1/09/2021
Loans
Keywords: Structural adjustment (Economic policy); Economic assistance